Humor styles and borderline personality. (December 2015) - Schermer, Julie Aitken; Martin, Rod A.; Martin, Nicholas G.; Lynskey, Michael T.; Trull, Timothy J.; Vernon, Philip A.
Abstract: The present study examined the phenotypic, genetic, and environmental correlations between four humor styles (affiliative, self-enhancing, aggressive, and self-defeating) and four dimensions of borderline personality disorder (affective instability, identity disturbance, negative relationships, self-harm) as well as a total borderline personality disorder score. Participants were 574 same-sex Australian adult twin pairs. At the phenotypic level, the two adaptive humor style dimensions (affiliative and self-enhancing) were found to correlate negatively with borderline personality and the two maladaptive humor style dimensions (aggressive and self-defeating) were found to have positive correlations with borderline personality. Bivariate genetic analyses demonstrated significant genetic, common environment, and unique environmental correlations. These results indicate that a large component of the phenotypic association between borderline personality disorder and humor style arises from the influence of shared familial and environmental factors associated with both phenotypes. Highlights: Adaptive humor styles correlated negatively with borderline personality. Maladaptive humor styles correlated positively with borderline personality. Many of the genetic and environmental correlations were significant.